Differential Effects of the Six Human TAU Isoforms: Somatic Retention of 2N-TAU and Increased Microtubule Number Induced by 4R-TAU - Bachmann, Sarah; Bell, Michael; Klimek, Jennifer; Zempel, Hans (Frontiers in Neuroscience, 2021)
In the adult human brain, six isoforms of the microtubule-associated protein TAU are expressed, which result from alternative splicing of exons 2, 3 and 10 of the MAPT gene. These isoforms differ in the number of N-terminal inserts (0N, 1N, 2N) and C-terminal repeat domains (3R or 4R) and are differentially expressed depending on the brain region and developmental stage. Although all TAU isoforms can aggregate and form neurofibrillary tangles, some tauopathies, such as Pick’s Disease and Progressive Supranuclear Palsy, are characterized by the accumulation of specific TAU isoforms. The influence of the individual TAU isoforms in a cellular context, however, is understudied. In this report, we investigated the subcellular localization of the human-specific TAU isoforms in primary neurons and analyzed TAU isoform-specific effects on cell area and microtubule dynamics in SH-SY5Y neuroblastoma cells. Our results show that 2N-TAU isoforms are particularly retained from axonal sorting and that axonal enrichment is independent from the number of repeat domains, but that the additional repeat domain of 4R-TAU isoform results in a general reduction of cell size and an increase of microtubule counts in cells expressing 4R-TAU isoforms. Our study points out that individual TAU isoforms may influence microtubule dynamics differentially both by different sorting patterns as well as by direct effects on microtubule dynamics.